Preservation of molecular fossils in carbonate concretions in cretaceous shales in the songliao basin, northeast China - Lin, Lamei; Cheng, Fuqi; Xu, Jinjun (Frontiers in Earth Science, 2023)
Paleoenvironment information is better preserved in carbonate concretions. Carbonate concretions in Cretaceous Nenjiang shale, Songliao Basin, were examined to determine if they better preserve molecular fossils reflective of the paleoenvironment. The organic and inorganic geochemical information of concretions and surrounding rocks were analyzed using a series of techniques including SEM, LA-ICP-MS, GC-MS-MS, and GC-IRMS. The results show that the biomarkers of concretions show similar distribution characteristics with those of surrounding rocks. This suggests that molecular fossils preserved in concretions were mainly inherited from surrounding rocks. However, the concretions contain more C27 sterane and hopanes, with the hopane/sterane ratio being significantly larger than that of surrounding rocks (1.49 v. 0.86), and their relative content of 2-methylhopane is 2.4 to 6.6 times that in the surrounding rocks. This indicates changes in the biological equilibrium of source organisms inside and outside the concretions. Possibly, the unstable organic matter as the core increased the bacterial concentration and activity inside the concretions. The HI and biomarker-derived indicators both imply that the transformation of organic matter in concretions is minimized relative to their host rock. The isotope δ13C16-30 of individual N-alkane hydrocarbons in the concretions is 1‰ to 3‰ more prevalent than that in surrounding rocks, which probably results from differences in the lithology, bacterial action, and degree of weathering. The research concludes that in-depth organic geochemical analysis on concretions can provide a valuable reference for research into early life.